A Casual Relationship Model of Accountants’ Knowledge and Skills Affecting Quality of Financial Report - Techatanaset, Pattra (Parichart Journal, 2019)
The purpose of the study is to study a causal relationship model of the accountants’ knowledge and skills that affect the quality of financial reporting. The research samples were 292 accountants in registered business in Bangkok. Questionnaires were used as a tool in research. Data was analysed by SPSS and AMOS program. Independent variables are the knowledge and skills of accountants. Dependent variable is quality of financial report. The results of the study showed that the model obtained from the study associated with the assumption from literature review by adjusting the error variables (e) until associated with assumption from literature review. The model obtained from the study indicated that p-value was at 0.333, CMIN/df = 1.071, RMSEA = 0.016, and CFI = 0.997 associating with the assumption. These results suggested that the knowledge and skills of accountants effect the quality of financial reporting.